The Relationship between Industrial Practice Activities and Academic Values of Multimedia Department Students at SMKN 1 Depok with Work Readiness - Ahsan, Muhammad Zamani; Irianto, Wahyu Sakti Gunawan; Kirana, Karika Candra (Universitas Negeri Malang, 2022)
Work readiness is highly important for prospective job seekers to become professionals in the working world. Some of them attend vocational schools (SMK) as preparation for entering the workforce. SMK offers industrial practice activities to familiarize students with the working world. Additionally, academic achievements are the results of students attending SMK. This research aims to find the correlation between industrial practice activities (x1) and academic achievements (x2) with work readiness (y). This research uses a quantitative approach with a descriptive correlational model. The research sample is multimedia department students at SMKN 1 Depok who have already completed industrial practice activities. Hypothesis testing uses Spearman correlation and multiple correlation. The results indicate a significant correlation between x1 and y, no significant correlation between x2 and y, and a significant correlation between x1 and x2 simultaneously with y.